Applicant2019;s Observations of the Communication from the Examining Division Dated 11.10.2018 (Global Journal of Science Frontier Research, 2019)
Under normal circumstances every Patent Application describes some step that explains something unknown in the Prior Art That is a well-known notion of Inventive Step